Enhanced electron transport through template-derived pore channels in dye-sensitized solar cells - Phadke, Sarika; Du Pasquier, Aurelien; Birnie, Dunbar P. (Journal of Physical Chemistry C, 2011)
Dye-sensitized solar cells use porous nanoparticle TiO(2) coating as their photoanode. To obtain effective dye adsorption and better electrolyte permeation in the TiO(2) coating, the porosity structure must be fully, three-dimensionally interconnected. Templated processing offers the advantage of preparing TiO(2) photoanodes in controlled shape and interconnection to the porosity structures that result, including the creation of dual size scale porosity in some cases. In the present work, an emulsion templating method was employed to obtain the dual porosity in the titania coating. We have studied the effect of the enhanced permeation of the electrolyte provided by these interconnected pore channels using electrochemical impedance spectroscopy. The change in internal resistances of the dye-sensitized solar cell during operation is correlated with the microstructural features using scanning electron microscopy, mercury porosimetry and I-V characterization.